2019
DOI: 10.1093/jxb/erz255
|View full text |Cite
|
Sign up to set email alerts
|

Lethal heat stress-dependent volatile emissions from tobacco leaves: what happens beyond the thermal edge?

Abstract: Natural vegetation is predicted to suffer from extreme heat events as a result of global warming. In this study, we focused on the immediate response to heat stress. Photosynthesis and volatile emissions were measured in the leaves of tobacco (Nicotiana tabacum cv. Wisconsin 38) after exposure to heat shock treatments between 46-55 °C. Exposure to 46 °C decreased photosynthetic carbon assimilation rates (A) by more than three-fold. Complete inhibition of A was observed at 49 °C, together with a simultaneous de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 168 publications
2
20
0
Order By: Relevance
“…Presence of LOX compounds in the emission blend typically indicates severe stress; LOX emissions can be induced upon mechanical damage, heat, ozone, and herbivory stresses, and the rate of LOX compound emissions often scales with the severity of stress [ 20 , 102 , 103 , 104 ]. O 3 exposure enhanced LOX compounds emission across all treatments, but comparison of WS and WW 550 ppb O 3 -treated plants, demonstrated that WW plants reacted more strongly (significant water stress effect; Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of LOX compounds in the emission blend typically indicates severe stress; LOX emissions can be induced upon mechanical damage, heat, ozone, and herbivory stresses, and the rate of LOX compound emissions often scales with the severity of stress [ 20 , 102 , 103 , 104 ]. O 3 exposure enhanced LOX compounds emission across all treatments, but comparison of WS and WW 550 ppb O 3 -treated plants, demonstrated that WW plants reacted more strongly (significant water stress effect; Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
“…LOX pathway volatiles like ( Z )-3-hexen-1-ol, 1-hexanol, 1-penten-3-ol, 1-penten-3-one together with 2-ethylfuran ( Table 2 ) were characteristic only to the WW and WS plants exposed to 550 ppb O 3 . Next to typical LOX compounds, we have observed previously that 2-ethylfuran is one of the signals of a severe stress as its emissions increased in N. tabacum and B. nigra after a threshold temperature was exceeded [ 47 , 104 ]. It is proposed that 2-ethylfuran is formed from ( E )-2-hexenal and co-emitted with ( Z )-3-hexenol [ 110 , 111 ], and 2-ethylfuran was observed in WW 550 ppb O 3 -treated plants in our study as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, acetaldehyde, ethanol, and acetone are often produced in roots, phloem or cambial tissues (Kimmerer and Stringer 1988;Rissanen et al 2020) where they remain dissolved until they reach the leaves via the transpiration stream within the plant (Rissanen et al 2018). Some of them, especially methanol and acetaldehyde are indicators of high metabolic activity, often found when tissue damage occurs (Fall et al 1999;Kreuzwieser et al 1999;Loreto et al 2006;Portillo-Estrada et al 2015;Turan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The start of isoprene release was associated with the heat stress itself as it correlated with LOX compound emissions both under priming and under the heat shock treatments (Figures 2a,b and 6d). Isoprene might be produced non‐enzymatically in stressed plants when the pool size of dimethylallyl diphosphate (DMADP) or isopentenyl diphosphate (IDP) builds up or pH rapidly changes in chloroplasts (Brilli et al, 2011; Silver & Fall, 1991; Turan et al, 2019; Velikova, Pinelli, & Loreto, 2005). Alternatively, the isoprene from heated A. millefolium foliage could be produced by multi‐substrate terpene synthases such as myrcene synthase in Humulus lupulus that can synthesize both isoprene and other terpenes depending on corresponding substrate availabilities (Pazouki & Niinemets, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites including terpenoids and phenolics have been demonstrated to play an important role in facilitating plant resistance and acclimation to extreme heat stresses by potentially directly improving heat tolerance or serving as antioxidants reducing the extent of lesion development after heat stress (Holopainen & Gershenzon, 2010; Loreto & Schnitzler, 2010; Possell & Loreto, 2013). Heat stress‐dependent damage can lead to immediate emissions of LOX and terpenoids that are either stored or de novo synthesized (Kask et al, 2016; Pazouki et al, 2016; Turan et al, 2019) and a longer‐term accumulation of phenolics continuing for hours to days after stress exposure (Sgarbi, Fornasiero, Lins, & Bonatti, 2003; Yoshikawa et al, 2018). Such response patterns involving progressive syntheses of terpenoids and phenolics provides an efficient means to cope with enhanced plant oxidative status in stressed plants (Liu, Marques dos Santos, Kanagendran, Neilson, & Niinemets, 2019).…”
Section: Introductionmentioning
confidence: 99%